2022
DOI: 10.3389/fmicb.2022.923242
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bacillus subtilis strain Z-14 on microbial communities of wheat rhizospheric soil infested with Gaeumannomyces graminis var. tritici

Abstract: Wheat take-all disease caused by Gaeumannomyces graminis var. tritici (Ggt) spreads rapidly and is highly destructive, causing severe reductions in wheat yield. Bacillus subtilis strain Z-14 that significantly controlled wheat take-all disease effectively colonized the roots of wheat seedlings. Z-14 increased the metabolic activity and carbon source utilization of rhizospheric microorganisms, thus elevating average well-color development (AWCD) values and functional diversity indexes of soil microbial communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…Ascomycota constituted the greatest proportion (17.82-58.43%), followed by Basidiomycota and Mortierellomycota in all samples (Figure 1 and Table S1). Liu et al [9] similarly reported that Ascomycota was the major phylum, accounting for 68.75-78.30% of the total fungal OTUs, obtained from wheat rhizospheric soil samples, followed by Mortierellomycota and Basidiomycota, which is consistent with the present results. These findings imply a similarity in the structure of the rhizospheric fungal communities of plants growing in the field or a greenhouse, and also among different plant species and soil types, suggesting that the rhizospheric fungal community structure shows a high innate stability [36].…”
Section: Effects Of Bacillus Bf1 and Y37 On Fungal Community Structur...supporting
confidence: 92%
See 1 more Smart Citation
“…Ascomycota constituted the greatest proportion (17.82-58.43%), followed by Basidiomycota and Mortierellomycota in all samples (Figure 1 and Table S1). Liu et al [9] similarly reported that Ascomycota was the major phylum, accounting for 68.75-78.30% of the total fungal OTUs, obtained from wheat rhizospheric soil samples, followed by Mortierellomycota and Basidiomycota, which is consistent with the present results. These findings imply a similarity in the structure of the rhizospheric fungal communities of plants growing in the field or a greenhouse, and also among different plant species and soil types, suggesting that the rhizospheric fungal community structure shows a high innate stability [36].…”
Section: Effects Of Bacillus Bf1 and Y37 On Fungal Community Structur...supporting
confidence: 92%
“…The endospores formed by Bacillus spp. Are highly resistant to heat and desiccation; these properties enable their development into commercial products that can be easily stored and have a long shelf life [ 8 , 9 ]. Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the application of Bacillus increased the closeness of the rhizosphere bacterial communities in the two soils, especially by increasing the diversity and complexity of the interactions between bacteria in red soil and increasing the degree of aggregation. These findings are consistent with those of Liu et al who similarly showed that the microbial agent B. subtilis Z-14 could enhance the network integrity of wheat rhizosphere bacterial communities [54]. However, due to the large number of microbial groups with large differences in abundance in the two soils, it is not yet possible to accurately determine the specific groups that can inhibit or promote the growth of Bacillus.…”
Section: Application Of Bacillus Significantly Promoted Phosphate Upt...supporting
confidence: 90%
“…In some cases, the microbial inoculants may compete with the native microbes for resources, which can result in a decrease in the abundance of these native microbes (Qiu et al, 2019 ). However, in other cases, the microbial inoculants may interact with the same genus of microbes in a positive way, which can enhance the overall functioning of the soil ecosystem (Liu et al, 2022 ). This positive relationship between microbial inoculants and the same genus of microbes in the soil highlights the potential of microbial inoculants to work in concert with existing microbial communities, resulting in a more robust and resilient soil ecosystem.…”
Section: Discussionmentioning
confidence: 99%